Morphology of pulmonary extralobar sequestration in neonatal death by hyaline membrane disease - Pegado, Claudia Schwartz (1994)
Fundação Oswaldo Cruz. Instituto Fernandes Figueira. Departamento de Anatomia Patológica. Rio de Janeiro, RJ, Brasil.